Advanced optimal control approaches for immune boosting and clinical treatment to enhance dengue viremia models using ABC fractional-order analysis - Vijayalakshmi, G. M.; Ariyanatchi, M.; Cepova, Lenka; Karthik, Krishnasamy (Frontiers in Public Health, 2024)
Throughout this work, we focused on the Dengue-viremia ABC (Atangana-Baleanu Caputo) fractional-order differential equations involving both symptomatic and asymptomatic infected cases. Symptomatic infected cases were illustrated as having higher viremia levels, while asymptomatic infected cases had lower viremia levels. The fractional-order model was classified to understand its behavior and memory effects, highlighting its advantages over traditional models. The total population was divided into four compartments: susceptible, asymptomatic infected, symptomatic infected, and recovered. The model incorporated an immune-boosting factor for asymptomatic infected cases and clinical treatment for symptomatic infected cases. Additionally, we analyzed the positivity and boundedness to validate the model and conducted both local and global stability analyses for a comprehensive mathematical understanding. We employed the novel Adams-Bash numerical scheme for simulations, rigorously assessing the effectiveness of optimal control measures. Our findings demonstrate the potential for successful disease control strategies by showing that reproduction numbers must be reduced according to specific optimal control conditions to effectively mitigate disease outbreaks. This research advances our understanding of disease mechanisms and offers valuable insights into the utilization of optimal control techniques for disease management.